Promoting The Forgotten Local tales of Terengganu “Tujuh Puteri” in digital Interactive Comic Book for Teenager. - Mohd Shuib, Ahmad Sofiyuddin; Wan Abdul Hamid, Wan Nurfathiyyah (Idealogy Journal; Vol 7 No 2 (2022): Idealogy Journal (September 2022)DO - 10.24191/idealogy.v7i2.374, 2022)
Folktales is considered as a representation of our local cultural that plays an important role in delivering our image and identity in society. Preserving our local folktales is crucial to avoid from being forgotten or fade away, especially in this modern era where local folktales may face difficulties in adapting in the society. In this current society, Malaysian particularly lack of awareness regarding traditional Malaysian folktales. The development of modern technologies and sufficient gadgets that are primarily used by teenagers had affected their interest towards the local heritage of folktales and it has become an issue that Malay folktales are being swallowed by modernization, thus becoming less popular among teenagers. The main purpose of this research is to seek the effectiveness of forming an interactive comic book with adaptation of AR application into one of Terengganu local folktales ‘Tujuh Puteri’ as a preference for this research. The aim of this paper is to develop interest among teenagers towards the Malay local folktales.   Keywords: Malay Folktales, Terengganu local tales, Promoting, Interactive comic book, Argumented Reality, Tujuh Puteri, Teenagers